2017
DOI: 10.1155/2017/3517187
|View full text |Cite
|
Sign up to set email alerts
|

Resin Nanoceramic CAD/CAM Restoration of the Primary Molar: 3-Year Follow-Up Study

Abstract: This case report presents the clinical use of a resin nanoceramic CAD/CAM restoration of a primary second molar without successor in the form of a permanent second premolar tooth in a patient. Three-year follow-up of the case revealed that resin nanoceramic CAD/CAM restoration of the primary molar without successor achieved both aesthetics and function. Despite the high cost of treatment, this type of restoration should be considered if the retained tooth is expected to maintain functionality over the long ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…Finally, a total of 10 articles were included in the present review. The characteristics of the 10 articles are summarized in Table 2 [5][6][7][8][9][10][11][12][13]. The articles were published between 2010 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 10 articles were included in the present review. The characteristics of the 10 articles are summarized in Table 2 [5][6][7][8][9][10][11][12][13]. The articles were published between 2010 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Threeyear follow-up of the case revealed that resin nanoceramic CAD/CAM restoration of the primary molar without successor achieved both aesthetics and function. Despite the high cost of treatment, this type of restoration should be considered if the retained tooth is expected to maintain functionality over the long term (32).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are limited cases of restorations on primary teeth with CAD/CAM technology that are associated with the fabrication of inlays or onlays for a primary decayed tooth or the fabrication of an endocrown. 23…”
Section: Discussionmentioning
confidence: 99%